Reductive metalation of the uranyl oxo-groups with main Group-, d- and f-block metals - Zegke, Markus (The University of Edinburgh, 2015)
This thesis describes the reductive functionalisation of the uranyl(VI) dication by metalation of the uranyl oxo-groups (O=UVI=O), using reductants from Group I, Group II, Group IV, Group XII and Group XIII as well as from the lanthanide and actinide series of the periodic table. Chapter 1 introduces uranium and nuclear waste, and gives an introduction into uranium(V) chemistry. It further compares the chemistry of uranyl(V) to neptunyl(V), with a specific focus on solid state interactions. The chemistry of the Pacman calixpyrroles is briefly introduced. These macrocyclic ligands form the basis for the synthesis of uranyl Pacman, which represents the major uranyl complex investigated in this thesis. Chapter 2 describes the reductive and catalytic uranyl oxo-group metalation using Group XIII and Group I reagents. It presents the reductive uranyl alumination using di-(iso-butyl)-aluminium hydride and Tebbe’s reagent to form the first Al(III)- uranyl(V) oxo complexes (AlIII-O-UV=O). The chapter shows how the transmetalation of these aluminated uranyl(V) complexes with alkali metal hydrides and alkyls leads to the formation of mono-metalated alkali metal uranyl(V) complexes (MI-O-UV=O). The combination of these two reactions is developed into a catalytic synthesis of the latter. The use of elemental alkali metals is described as another pathway of accessing alkali metal uranyl(V) complexes, carried out in collaboration with Dr. Rianne M. Lord. Chapter 3 describes the synthesis of the first Group IV uranyl(V) complexes, using low-valent titanium and zirconium starting materials. The chapter includes magnetic measurements on the first Ti(III)-uranyl(V) complex and a comparison of computational results regarding a selection of uranyl(V) complexes from this thesis. The magnetic measurements were carried out by Dr. Alessandro Prescimone, University of Edinburgh, and analysed by Dr. Nicola Magnani, Institute for Transuranium Elements, Karlsruhe, Germany. Theoretical calculations were carried out by Xiaobin Zhang and Prof. Dr. Georg Schreckenbach, University of Manitoba, Canada. The chapter further describes the reductive metalation of uranyl using elemental Mg, Ca and Zn and their respective metal halides. Chapter 4 describes the uranyl functionalisation using f-elements and their complexes. It describes the attempted mono-metalation using lanthanides and the formation of a Sm(III)-bis(uranyl(V)) complex. It further describes the uranyl reduction using actinides and the synthesis of the first U(IV)-uranyl(V) complex. The chapter further describes the first Np(IV)-uranyl(V) complex and the attempted synthesis of a Pu(IV)-uranyl(V) complex. These syntheses were performed in collaboration with Michał S. Dutkiewicz at the Institute for Transuranium Elements (ITU) in Karlsruhe, Germany. This work was carried out with the help of Dr. Christos Apostolidis and Dr. Olaf Walter and supervised by Prof. Dr Roberto Caciuffo. Chapter 5 describes the reductive uranyl functionalisation in a redox-active dipyrromethene ligand, collaboratively carried out with James R. Pankhurst and Lucy N. Platts. The synthetic work and analyses were performed jointly with Lucy N. Platts (master student under the supervision of the author); UV-vis spectra and cyclic voltammograms were recorded by James R. Pankhurst and Lucy N. Platts. The chapter presents the synthesis of a new uranyl(VI) complex and its two-electron reduction to uranium(IV) using a titanium(III) reductant. Additionally the chapter describes the reductive uranyl silylation in a dipyrromethane complex of which the ligand was designed by Dr. Daniel Betz. Section 6 describes the synthetic procedures. Section 7 gives references to the work of others. Section 8 shows the publication related to this thesis. Section 9 is a table of the complexes described in this thesis.
Keywords: uranyl; actinides; nuclear; oxo